Determinan Audit Report Lag pada Perusahaan Sektor Pertambangan dan Properti & Real Estate yang Terdaftar di BEI Tahun 2019–2021 dengan Kepemilikan Manajerial sebagai Variabel Moderasi - Jessica, Meryana; Rusmita, Sari; Damayanti, Fera (Jurnal KIAFE, 2024)
This study aims to examine the effects of leverage, profitability, and audit committee size on audit report lag, as well as the moderating role of managerial ownership in the relationships between leverage, profitability, audit committee size, and audit report lag. The population consists of mining and property and real estate sector companies listed on the Indonesia Stock Exchange during the 2019–2021 period. This study employs a quantitative approach using secondary data obtained from the official website of the Indonesia Stock Exchange. The data were analyzed using multiple linear regression analysis and Moderated Regression Analysis. The analytical procedures included descriptive statistical analysis, classical assumption tests, and hypothesis testing using SPSS version 25.0. The results indicate that leverage has no significant effect on audit report lag, while profitability and audit committee size have significant effects on audit report lag. Furthermore, managerial ownership does not significantly moderate the effects of leverage, profitability, and audit committee size on audit report lag.